Inovasi produk keuangan mikro syariah dalam mendukung perluasan usaha umkm di sektor industri kreatif halal di daerah pedesaan - Khasanah, Uswatun (Maliki Interdisciplinary Journal, 2025)
MSMEs not only play an important role in absorbing labor and strengthening the structure of the local economy, but also serve as a means for equitable distribution of community income. However, MSME players in this sector often face major obstacles in the form of limited access to financing that is in accordance with sharia principles and the characteristics of their businesses. The purpose of writing this article is to find out the Innovation of Sharia Microfinance Products in Supporting MSME Business Expansion in the Halal Creative Industry Sector in Rural Areas. The type of research in this study is library research, namely research through literature or literature studies. Islamic microfinance product innovation plays an important role in encouraging the development and expansion of MSME businesses in the halal creative industry sector, especially in rural areas. Through the application of sharia principles integrated with digital technology and empowerment approaches, a more inclusive, equitable and sustainable business ecosystem is created. This innovation not only offers capital solutions, but also contributes to increasing production capacity, developing more diverse businesses, and expanding market networks at local, national and international levels.